Male migration and its Impact on women in Kapilbastu (Journal of Population and Development, 2024)
Although males are generally thought to be the ones who migrate internationally, women who were not migrants nonetheless suffer significant effects as a result of the migration of their male counterparts. Left behind women given second-class status in relation to men, this presents both a difficulty and an opportunity. Women who are more capable not only have more independence and overall well-being, but their improved abilities also have a favorable impact on the lives of friends and family. Women are capable of handling situations effectively when given the opportunity to assume responsibility for social, political, and economic facets of life. From this perspective, the primary objective of this study is to identify the variables influencing women's empowerment in Kapilbastu Municipality. Similarly, the secondary goal of the study is to determine how international migration affects the situation of women who are left behind in the study region. From the research region, 50 migrant households and 50 non-migrant households were chosen using purposive sampling method. As per the results of the study, male migration abroad has significantly contributed to their enhanced abilities and increased engagement in outdoor pursuits. They made a lot of wonderful friends, learned a lot about the outside world, experienced sharing, learned how to interact with people outside, and generally had a positive outlook on life as a result of their engagement in outdoor activities.